Fault Diagnosis Method for Control Circuit of ZDJ9 Double-machine Traction Speed-up Turnout Electric Switch Machine - TANG Shaojie; TANG Kaize; GUO Lei; CUI Chen (Chengshi guidao jiaotong yanjiu)
［Objective］ In the ZDJ9 double-machine traction speed-up turnout electric switch control circuit, 1DQJ is an instantaneous suction relay. When the outdoor switch circuit does not form a loop, that is, in the event of a fault, the 1DQJ relay only maintains a short-term suction state for about 1s. When dealing with the fault point, technicians usually use a multimeter to measure. A digital multimeter can only flash once for a short period of time within 1 second, and the maximum displayed data is about 170 V; the pointer of a pointer multimeter can only swing slightly in 1 second, and it only swings to about 120 V, making it impossible to conduct a detailed search for the fault point. On the other hand, the control circuit adopts a 380 V three-phase AC power supply, which may ignite during the troubleshooting process. Due to the fear of technicians, the troubleshooting is slow, time-consuming, labor-intensive, and safety is greatly compromised. Innovative research is conducted on the common problems currently existing, and targeted fault diagnosis devices and methods are proposed. ［Method］ Three 200W light bulbs are combined to form a bulb diagnostic device, sharing one grounding electrode, and the other polarity is connected to the A, B, and C three-phase power supply. The bulbs are connected by the instantaneous suction of the 1DQJ relay. If the light is on, it means that there is no fault in the circuit. If the light is off, it means that there is a fault. The method of finding faults using the A, B, and C three-phase power supply is explained in detail. ［Result & Conclusion］ The proposed fault point diagnosis device and method can accurately and quickly diagnose the fault point of the control circuit and greatly improve the safety in fault diagnosis.